Introduction to adaptive arrays - Monzingo, Robert A., 1938- (SciTech Pub., 2011)
The following topics are dealt with in this book: adaptive array fundamental principles: system uses, system elements, basic concepts, and optimum array processing; and adaptive algorithms.
Keywords: Antenna arrays.; elektronické knihy; electronic books